Relevansi Filosofi Androgenitas Carl Gustav Jung bagi Pendidikan Adil Jender - Hastanti Widy Nugroho (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
The Relevance of Carl Gustav Jung's Philosophy on Androgynity to the Gender Equality in Education. Androgynity concept means that everyone carries within them the feminine and masculine aspects as two eternal images, coexisting as equal and complementary parts of balanced cosmic system. Androgynity concept functions as a pair of opposites complementary, profoundly influencing the relation of all men and women with each other. Based on the research, understanding androgynity concept is important to make both man and women become consciuos of each other's psychic reality and have consciousness of gender equality, mainly in education. Androgynity concept is needed as alternative solution to gender inequality problem in education.